(3GdHjY GdTNUj h GdJShjb GdeHGTQs - (3MejO(B, (3GdWGFjs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2009)
(3WHjYI h OhQ GdHjY , GdJhLg GdHjYj ddJShjb ebGHd GdJhLg GdMOjK ddJShjb , NUGFU GdHjY GdMOjK , CTcGd GdHjY , COhGJ GdHjY GdTNUj h eSGgeGJg , GdaQhbGJ Hjf GdHjY GdJbdjOj h GdHjY GdMOjK , GdeOGNd GdNeSI ddHjY GdTNUj , GdeQGMd GdQFjSjI aj YedjI GdHjY GdTNUj , egGQGJ GdHjY h CfhGY GdYedGA h cjajI GdJYGed eYge , eGPG jQjO GdYejd (B( (3GdRHhf (B) (3, cja JJYGed eY GdYejd Ch GdRHhf , GdJShjb GdejGTQ h GdfehPL GdLOjO dg , feh h efGaY GdJShjb , CTcGd GdJShjb , GdNWI GdJShjbjI (B: (3eONd eaGgjej ddJNWjW , ebheGJ h eHGOF GdJNWjW GdJShjbj GdaYGd , CZQGV GdNWI GdJShjbjIs
(3eQGLY U(B.96(3,(B136(3,(B180 ((3EbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdHjYs; (3GdHjY GdeHGTQs; (3GdJShjbs